Pengaruh Pemberian Insentif dan Lingkungan Kerja terhadap Tingkat Perputaran Karyawan Dealer Mobil DFSK Palembang - Hannia, Hannia; Roswaty, Roswaty; Emilda, Emilda (Training & Research Institute - Jeramba Ilmu Sukses, 2023)
This study deals with the effect of providing incentives and the work environment on the employee turnover rate of the DFSK Palembang Car Dealer simultaneously on the turnover rate. This type of research was quantitative research which employed the associative method. The data collection technique used is a questionnaire. The sample population used in this study was 40 employees of the DFSK Palembang Car Dealer. The data analysis technique in this study used multiple regression analysis. The results of this study using the t-test partially show that the Incentive Giving variable (X1) has a significant effect on the employee turnover rate. Then the Work Environment variable (X2) has a significant effect on the level of employee turnover. The results of testing the F test showed simultaneously that the Incentive Giving variable (X1) and Work Environment (X2) had a significant effect on the employee turnover rate. This research can be expected to conduct companies to evaluate the provision of employee incentives and work environment to reduce employee turnover